The volcanology, geochemistry and metallogenic potential of the goren volcano-sedimentary belt, northeast Burkina Faso, West Africa - Peters, Luke Fred Horst (My University, 2014)
The Palaeoproterozoic southern Goren volcano-sedimentary belt of northeast Burkina Faso represents a sequence/package of rocks formed in a back-arc basin environment. Evidence is based on a conformable sequence of basalts that have geochemical affinities of normal mid-oceanic ridge style basalts (N-MORB) as well as arc-related magmas. Tholeiitic compositions, determined by major and trace element geochemistry, are exclusive to the study area, which is unique to northeast Burkina Faso. Flat, chondrite-normalised REE patterns suggest dominantly N-MORB compositions, with the occasional elevated Th and Al2O3 values, suggestive of arc basalts. Depleted chondrite-normalised concentrations of phosphorus (0.5-0.03 times lower than chondrite) and Ti (1-5 times chondrite) as well as anomalous concentrations of N-MORB-normalised Ta (80-120 times greater) are characteristic of the tholeiitic basalts of the Goren belt. The volcanic rocks are intercalated with a succession of volcanogenic manganese deposits, siltstone, volcaniclastite, volcanogenic greywacke and a discrete pyroclastic breccia deposit composed of lapilli- to bomb-sized volcanic debris, indicative of bimodal volcanism. The volcanic facies were established through field and petrographic interpretations. The subaqueous facies architecture consists of proximal, coherent and autoclastic basaltic flow units containing porphyritic, aphyric, amygdaloidal and hyaloclastic textures as well as pillowed, jointed and flow-banded basaltic lithofacies. Proximal to distal volcanogenic manganese deposits intercalated with basalt flows indicate a syn-volcanic genesis. A discrete pyroclastic interbed (~300 m thick) within a volcanogenic, marginal marine to offshore greywacke succession occupies a distal facies relative to the volcanic source and indicates a bimodal source of volcanism, i.e., mafic and intermediate. Volcanogenic manganese deposits are characterized by quartz-ankerite stockwork breccia, a braunite-ilmenite-magnetite-chalcopyrite-pyrite-(gold) mineral assemblage and increased Ba concentrations, indicating syn-volcanic seafloor-related hydrothermal activity. The Goren volcano-sedimentary belt presents potential for economic mineralisation in volcanogenic primary manganese and base metal deposits.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, December, 2013.
Keywords: Volcanoes.; Geochemistry.; Metallogeny.